-74:(+2)-3x[-2+4x(-3)]= ?
(800-160+120):(-19)-(-500) : (+5)-(-80):(-16)-(-11):(+11)=?
(-333+33-3):(-3)+(+3)x(-3)-(-33)x(-3)+(-333)x(-3)=?
[(-30):(+10)-(-8)x(+5)]:(37)=?
[(-175):(-25)-(-70):(-14)]x[(-40)x(+3)-(-25)x(-3)]=?
-5x{[-72):[(-8)x(+3)-(+40):(-4)+50]+(-18)x(-2):(-6)}=?
-12+12x{13-13x[-5-(-2)x-(-3)]-6}=?

1

Răspunsuri

Cel mai inteligent răspuns!
2014-05-13T22:45:54+03:00
-37 - 3*(-2-12)=
=-37 -3 *(-24)=
=-37 +72= 35

(920-160):(-19)- (-100)-(+5)-(-1)=
=(+760):(-19)+100 -5 +1=
=-40 +101-5=
=-45+101= -56

(-336+33):(-3)+(-9)-(+99)+999=
=(-303):(-3)-9-99+999=
=101 -108 +999=
=1100-108= 992

[(-3)-(-40)]:37=
=(-3+40):37=
=37:37=1

[7-(+5)]* [-120-(+75)]=
=(7-5)*(-120-75)=
=2*(-195)=-390

-5*{[-72:[-24-(-10)+50]+36:(-6)}=
=-5*[-72:(-24+10+50)-6]=
=-5*[-72:(-24+60)-6]=
=-5*(-72:36-6)=
=-5*(-2-6)=
=-5*(-8)= 40

-12+12*{13-13*[-5-(-2)*3]-6}=
=-12+12*{13-13*[-5-(-6)]-6}=
=-12+12*{[13-13*(-5+6)]-6}=
=-12+12*[(13-13*1)-6]=
=-12+12*(0-6)=
=-12+12*(-6)=
=-12-72= -84
2 4 2